Comparative Analysis of The Soundness of Conventional Foreign Exchange Banks Andsharia Foreign Exchange Banks Using RBBR Method Period 2015-2019 - Cindy Amelia Br Sembiring (International Journal of Applied Finance and Business Studies, 2020)
The purpose of this study is to analyze and test the differences of soundness level between conventional foreign exchange banks and sharia foreign exchange banks in Indonesia. The application of the assessment used RBBR method period 2015-2019. Research variables consist of Non Performing Loan, Loan to Deposit Ratio, Good Corporate Governance, Return on Assets, Operating Expenses on Operating Income, and Capital Adequacy Ratio. The data analysis methods used in this study were descriptive statistics, Independent-Sample T Test, and Mann–Whitney U test. The total sample in this study was 21 banks (16 conventional foreign exchange banks and 5 sharia foreign exchange banks) which were selected by using a purposive sampling technique. The results of this study indicate that there are significant differences in the NPL, LDR, ROA, BOPO.